If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6u + 2(u + -5) = 6 Reorder the terms: -6u + 2(-5 + u) = 6 -6u + (-5 * 2 + u * 2) = 6 -6u + (-10 + 2u) = 6 Reorder the terms: -10 + -6u + 2u = 6 Combine like terms: -6u + 2u = -4u -10 + -4u = 6 Solving -10 + -4u = 6 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -4u = 6 + 10 Combine like terms: -10 + 10 = 0 0 + -4u = 6 + 10 -4u = 6 + 10 Combine like terms: 6 + 10 = 16 -4u = 16 Divide each side by '-4'. u = -4 Simplifying u = -4
| y+2(-4)=0 | | X^2-x+15=113 | | 30=5(y+4)-7y | | (x-2)(x+3)(1-2x)=0 | | 2x(4x+8y)= | | y+2(-6)=0 | | 12/6/2*3 | | 6y-20-y=19-3(-12y-18) | | 12/6/2.3 | | u-11=18 | | -w/3-4 | | 16z=40 | | -7x=23/74 | | 12/6/2x3 | | 5(5p-9)-16=18p-2p-7 | | -2+10x+12= | | 24/3/5f | | 6(6x+6)-6(6+-6x)= | | -2+10x+10= | | y=9(4)-1 | | 2.25(4x-4)= | | 3x=3-8 | | 9(-r+14)=14-20r+18r | | y=9(3)-1 | | 3=9x-1 | | y=9x-14 | | -5(3x-9)=x | | w-59=18 | | 8=9x-1 | | (12x^2-27y^2)/(x^2-(x-3y)^2) | | 9x-(4x+11)=41 | | 7q-7(-8q-3)=3(20q-6) |